FCRL3 expression is upregulated and closely correlates with TIGIT expression in regulatory T cells of patients with systemic lupus erythematosus - Bahabayi, Ayibaota; Zhang, Ya‐Hui; Yuan, Zihang; Wang, Yiying; Zhang, Zhonghui; Zeng, Xingyue; Guan, Zhao; Wang, Pingzhang; Liu, Chen (European journal of immunology, 2024)
Using data from single‐cell RNA sequencing and flow cytometry, we initially examined the expression of FCRL3, finding it to be elevated and positively associated with TIGIT expression in the regulatory T cells of patients with systemic lupus erythematosus. This also suggests that the co‐expression of FCRL3 and TIGIT warrants further attention.